Polyamines Confer Salt Tolerance in Mung Bean (Vigna radiata L.) by Reducing Sodium Uptake, Improving Nutrient Homeostasis, Antioxidant Defense, and Methylglyoxal Detoxification Systems - Nahar, Kamrun; Hasanuzzaman, Mirza; Rahman, Anisur; Alam, Md. Mahabub; Mahmud, Jubayer-Al; Suzuki, Toshisada; Fujita, Masayuki (Frontiers in Plant Science, 2016)
The physiological roles of PAs (putrescine, spermidine, and spermine) were investigated for their ability to confer salt tolerance (200 mM NaCl, 48 h) in mung bean seedlings (Vigna radiata L. cv. BARI Mung-2). Salt stress resulted in Na toxicity, decreased K, Ca, Mg, and Zn contents in roots and shoots, and disrupted antioxidant defense system which caused oxidative damage as indicated by increased lipid peroxidation, H2O2 content, O2•– generation rate, and lipoxygenase activity. Salinity-induced methylglyoxal (MG) toxicity was also clearly evident. Salinity decreased leaf chlorophyll (chl) and relative water content (RWC). Supplementation of salt affected seedlings with exogenous PAs enhanced the contents of glutathione and ascorbate, increased activities of antioxidant enzymes (dehydroascorbate reductase, glutathione reductase, catalase and glutathione peroxidase) and glyoxalase enzyme (glyoxalase II), which reduced salt-induced oxidative stress and MG toxicity, respectively. Exogenous PAs reduced cellular Na content and maintained nutrient homeostasis and modulated endogenous PAs levels in salt affected mung bean seedlings. The overall salt tolerance was reflected in improved tissue water and chl content, and better seedling growth.